FRAMING OF AFGHAN CRISIS AFTER ASHRAF GHANI REGIME: A COMPARATIVE STUDY OF CNN AND AL JAZEERA WEB NEWS - Dr Rooh Ul Amin Khan; Yousaf Khan; Dr. Bin Yamin Khan (`, 2025)
The fall of the Ashraf Ghani regime in Afghanistan in August 2021, led the Taliban's return to power, garnered extensive international media attention. This study examines how CNN and Al Jazeera, framed the Afghan crisis in their web news during the first three months of Taliban government. Using quantitative content analysis, this research project focused on language, sources, thematic emphasis, and the portrayal of key actors. Preliminary findings indicate that CNN predominantly employed the "dominant crisis" theme, which underscores a perspective of instability and chaos while Al Jazeera heavily focused on the submissive crisis & reality view theme which emphasizes on grounded and factual perspectives of the crises. Despite these differences, both news organizations shared a common focus on the instability and uncertainty, though with varying emphases on causes and consequences & offers insights into the impact of media on global public opinion. Keywords: Afghan crisis, media framing, Taliban, conflict reporting